The expansion of available bioparts and the development of CRISPR/Cas9 for genetic engineering of Parageobacillus thermoglucosidasius - Lau, Matthew Simon Harold (2019)
Growing public concern over the environmental and health impacts caused by the use of fossil fuels, coupled with diminishing reserves, is now compelling the pursuit for an alternative source. The search for alternative methods to manufacture products conventionally derived from fossil fuels, has led to research into microbial conversion of lignocellulosic biomass into analogous derivatives. Though many well established renewable energy methods currently exist, research into the production of petroleum-based products, such as transportation fuel and platform chemicals, is currently insufficient. Second generation biofuels have successfully overcome numerous problems associated with original biofuel production; however, many challenges are prevalent for established mesophilic organisms such as Escherichia coli or Saccharomyces cerevisiae. Thermophilic species have been presented as a potential platform strain to circumvent these problems. Typically non-fastidious and catabolically flexible organisms, thermophiles can ferment both hexose and pentose sugars, facilitate lower overall fermentation costs and are generally more robust organisms, a trait valuable for industrial processes. Unfortunately, current genetic tools are not well established to achieve the necessary yields to replace both the fossil fuel industry and the currently used organisms.